Impact of Drying Methods on the Chemical Profile of Zingiber officinale Rosc. Rhizome Essential Oil. Issue 5 (3rd September 2022) - Aabha,; Tewari, Geeta; Pande, Chitra; Kanyal, Bhawana; Rana, Lata; Singh, Shalini
Abstract: Zingiber officinale Rosc. belonging to the family Zingiberaceae, is mentioned as Maha-aushadhi in Ayurveda and is also used in many processed dried ginger-based products. The present work was designed to determine the effect of drying on the essential oil content and composition of Zingiber officinale Rosc. rhizomes collected when matured, from Khatima, Uttarakhand region. The GC and GC/MS analysis of the oils resulted in the identification of total 56 (fresh), 45 (sun dried), 47 (blower dried), 37 (shade dried), 46 (oven dried at 30°C) and 44 (oven dried at 50°C) compounds representing 97.93 %, 98.48%, 98.26%, 99.25%, 99.10% and 98.65% of the total oil respectively. The predominant compounds in the oil were geranial (17.53-35.24%), neral (12.47-24.59%), β-phellandrene (9.84-14.12%), geraniol (5.43-10.19%), geranyl acetate (1.33-12.23%), camphene (4.45-7.87%) and zingiberene (0.92-5.24%). The content of camphene, β-phellandrene and geranyl acetate decreased while the percentage of geranial, neral, geraniol and zingiberene increased on drying the ginger rhizomes. The essential oil of all the samples had high percentage of oxygenated monoterpenes. This study was one of its kind and showed a significantly different deduction from other studies.